The political economy of the African pharmaceutical sector's “industrial underdevelopment” lock-in: The importance of understanding the impact of persistent colonial extractive institutions - Banda, Geoffrey (Frontiers in Research Metrics and Analytics, 2023)
The bedrock of systems of innovation is the central role innovation plays in national competitiveness and economic performance/development. Built on this foundation, science, technology and innovation policies are designed to support the generation, appropriation and extraction of value from knowledge systems for societal benefit. On the other hand, political economy determines who has power and wealth and how they are distributed in society thereby determining economic outcomes. Applying these lenses to the African pharmaceutical sector is not so straightforward. Historical economic development trajectories established on the back of extractive institutional set-up and circumscription of industrial activities away from high-value, knowledge intensive manufacturing sectors shaped current industrial structures on the African continent. The African pharmaceutical manufacturing sector was afflicted by the persistence of extractive institutions. I focus on why an African pharmaceutical sector set up as early as the 1930s and biologics manufacture dating to the 1890s has not significantly developed. I focus on four institutional areas: the scarcity of institutions for pharmaceutical policy design at national level; institutional challenges in financing innovation and research, industry development and entrepreneurship; and draw lessons from the UK’s regenerative medicine sector to underscore the importance building new institutions to support early stage technology development and de-risking as well as value chain gap bridging institutions; and building local regulatory and technological capabilities.